2015
DOI: 10.1136/annrheumdis-2015-eular.5292
|View full text |Cite
|
Sign up to set email alerts
|

FRI0620-HPR Weight Loss Intervention Before Total Knee Arthroplasty – Feasibility and Safety

Abstract: BackgroundAnnually 8500 total knee arthroplasty (TKA) are performed in Denmark. About 80% of this population is overweight or obese. The present material is part of a longitudinal randomized study (ClinicalTrial.gov: NCT01469403).ObjectivesTo investigate whether it is feasible and safe to implement an intensive weight loss program in order to reduce preoperative body weight of obese patients before TKA surgery. The primary aim of the Weight Loss Intervention before Total Knee Arthroplasty (WITKA) study is to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Of these, eight records passed the initial screening of the title and abstract review (six full-length articles and two abstracts) and were assessed for eligibility (see Fig. 1 ) [ 9 , 25 31 ]. A total of four records met the inclusion criteria (two cohort studies, two RCT abstracts).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, eight records passed the initial screening of the title and abstract review (six full-length articles and two abstracts) and were assessed for eligibility (see Fig. 1 ) [ 9 , 25 31 ]. A total of four records met the inclusion criteria (two cohort studies, two RCT abstracts).…”
Section: Resultsmentioning
confidence: 99%
“…A total of four records met the inclusion criteria (two cohort studies, two RCT abstracts). The two intervention studies were only available in abstract format at the time of the review [ 30 , 31 ]. We contacted the authors of these abstracts to determine if a full-length article had since been published.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three studies of pre-operative dietary interventions involving some amount of time prior to TJA, though just one measured pre-operative weight loss while the remaining two studies only measured postoperative weight as endpoints. Liljensøe et al randomized 77 participants to a standard care control group or a dietician supervised weight loss group that consisted of nutrition education group sessions and a low calorie (810 kcal/day) diet using formula foods for 8 weeks before surgery, followed by a 1-year maintenance period after surgery [12]. Intervention participants lost an average of 10.7 kg in the 8 weeks before surgery, and the authors concluded that a pre-operative weight loss program shortly before TJA was safe to implement.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite multiple investigations regarding the association between lifestyle interventions and postoperative outcome, there is a dearth of research regarding success of weight loss interventions specifically prior to TJA. Although there are three studies of pre-operative dietary interventions prior to TJA, only one study concluded before surgery and this study did not compare pre-operative weight loss to a control group [12][13][14]. A 2015 review of nonsurgical, non-pharmacologic weight loss interventions in patients with obesity prior to TJA found that there was limited research on the association between weight loss prior to TJA and pre-and post-operative outcomes, and that future studies should address the safety, optimal timing, duration, amount of targeted weight loss, and delivery of pre-TJA interventions [15].…”
Section: Introductionmentioning
confidence: 96%